Redesigning Nigeria's financial system : a study of Nigeria at the financial crossroad in applied financial intermediation - Falegan, S. B. (Ibadan : University Press Limited, 1987)
The book examines the problems facing the Financial System as deriving largely from the consequences of both the nation's economic problems and of the financial system policies. Apart from being under banked, financial intermediaries that can be employed to mobilize rural savings and development are virtually non-existent. The Central Bank is constrained in its authority and control over monetary policy and management. The book then proffers solutions to these problems by broadening the financial and real asset base, and provide resources for a long-term development.
Includes index.
Includes bibliographical references: p. 410-422.
rpm 27/04/2018, ijb 11/03/2019
Loans
Keywords: Finance; Financial institutions; Monetary policy; Banks and banking; Banks and banking, Central